Self-Confirming Equilibrium and Model Uncertainty - Battigalli, Pierpaolo; Cerreia-Vioglio, Simone; Maccheroni, Fabio; Marinacci, Massimo (American Economic Review, 2015)
We analyze a notion of self-confirming equilibrium with non-neutral ambiguity attitudes that generalizes the traditional concept. We show that the set of equilibria expands as ambiguity aversion increases. The intuition is quite simple: by playing the same strategy in a stationary environment, an agent learns the implied distribution of payoffs, but alternative strategies yield payoffs with unknown distributions; increased aversion to ambiguity makes such strategies less appealing. In sum, a kind of “status quo bias” emerges; in the long run, the uncertainty related to tested strategies disappears, but the uncertainty implied by the untested ones does not. (JEL C72, C73, D81, D83)